What drives rice farmers away from straw burning? Evidence from the Mekong Delta, Vietnam - Cuong, Ong Quoc; Demont, Matty; Pabuayon, Isabelita M.; Depositario, Dinah Pura T. (Elsevier, 2025)
The Asian mega deltas are critical for food security since they are among the most productive regions for rice cultivation globally. However, this comes at the expense of their environment. Rice growing produces straw, which is frequently burned, resulting in considerable atmospheric pollution and greenhouse gases. Previous research in the Mekong Delta has suggested that policy makers can incentivize rice farmers to transition from straw burning to sustainable straw management practices by creating an enabling environment to support farmers in achieving economies of scale through collective governance of straw management and mechanization of straw collecting and processing. However, little is known about the drivers of rice straw burning in the Mekong Delta. To address this gap, we surveyed 543 rice farmers in four provinces in the Mekong Delta in Vietnam. A multinomial logistic regression was used to examine the determinants of the adoption of alternative straw management practices. The survey results indicate that straw burning is practiced by 45–84% of rice farmers, depending on the season. The results from the model reveal that straw burning peaks in the Winter-Spring cropping season in An Giang province and is more likely to be practiced by larger or contract farms, while sustainable straw management practices are more frequently adopted by wealthier households or farms that receive agricultural extension services. These findings confirm the importance of agricultural extension programs in achieving economies of scale in sustainable straw management. Policy makers can leverage and scale the adoption of sustainable straw management through public extension programs and by encouraging companies to govern and support these practices through private extension in their production contracts.